Treasures of Nome: Endless Mercy - Book 2 - Peterson, Tracie; Woodhouse, Kimberley 1973- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2021)
"In 1891, when Madysen Powell's supposedly dead father shows up, her gift for forgiveness is tested and she's left searching for answers. Daniel Beaufort arrives in Nome, longing to start fresh after the gold rush leaves him with only empty pockets, and finds employment at the Powell dairy. Will deceptions from the past tear apart their hopes for a better future?"--
Keywords: Farm life -- Fiction; Nome (Alaska) -- Fiction; Christian Historical fiction; Love stories; Novels